Bactericidal Effects of 405 nm Light Exposure Demonstrated by Inactivation of Escherichia, Salmonella, Shigella, Listeria, and Mycobacterium Species in Liquid Suspensions and on Exposed Surfaces - Lynne E. Murdoch; Michelle Maclean; Endarko Endarko; Scott J. MacGregor; John G. Anderson (The Scientific World Journal)
The bactericidal effect of 405 nm light was investigated on taxonomically diverse bacterial pathogens from the genera Salmonella, Shigella, Escherichia, Listeria, and Mycobacterium. High-intensity 405 nm light, generated from an array of 405-nm light-emitting diodes (LEDs), was used to inactivate bacteria in liquid suspension and on exposed surfaces. L. monocytogenes was most readily inactivated in suspension, whereas S. enterica was most resistant. In surface exposure tests, L. monocytogenes was more susceptible than Gram-negative enteric bacteria to 405 nm light when exposed on an agar surface but interestingly less susceptible than S. enterica after drying onto PVC and acrylic surfaces. The study findings, that 405 nm light inactivates diverse types of bacteria in liquids and on surfaces, in addition to the safety advantages of this visible (non-UV wavelength) light, indicate the potential of this technology for a range of decontamination applications.